2019
DOI: 10.3390/ijms20092304
|View full text |Cite
|
Sign up to set email alerts
|

Control Mechanisms of the Tumor Suppressor PDCD4: Expression and Functions

Abstract: PDCD4 is a novel tumor suppressor to show multi-functions inhibiting cell growth, tumor invasion, metastasis, and inducing apoptosis. PDCD4 protein binds to the translation initiation factor eIF4A, some transcription factors, and many other factors and modulates the function of the binding partners. PDCD4 downregulation stimulates and PDCD4 upregulation inhibits the TPA-induced transformation of cells. However, PDCD4 gene mutations have not been found in tumor cells but gene expression was post transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 104 publications
5
118
0
Order By: Relevance
“…TPA (12-O-tetradecanoylphorbol-13-acetate), a potent stimulator of protein kinase C (PKC), also induces the phosphorylation and degradation of PDCD4 protein. The TPA-activated PKCδ and PKCε signaling pathways phosphorylate PDCD4, leading to its degradation by the proteasome system in Huh7 hepatocellular carcinoma cells [18,25,26]. During the investigation of PDCD4 degradation mechanisms, we found that the proteasome inhibitor MG132 slightly upregulated the PDCD4 protein levels in Huh7 cells [26].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…TPA (12-O-tetradecanoylphorbol-13-acetate), a potent stimulator of protein kinase C (PKC), also induces the phosphorylation and degradation of PDCD4 protein. The TPA-activated PKCδ and PKCε signaling pathways phosphorylate PDCD4, leading to its degradation by the proteasome system in Huh7 hepatocellular carcinoma cells [18,25,26]. During the investigation of PDCD4 degradation mechanisms, we found that the proteasome inhibitor MG132 slightly upregulated the PDCD4 protein levels in Huh7 cells [26].…”
Section: Introductionmentioning
confidence: 88%
“…The PDCD4 mRNA expression is silenced by methylation at the 5 CpG island of the PDCD4 promotor region [17]. However, PDCD4 gene mutations have not been reported and the expression is mostly controlled post transcriptionally at translation and protein degradation levels [18]. MicroRNAs (miRNAs), which are endogenous non-coding small RNAs, bind to the 3 -UTR region of the transcript and induce either translational suppression or degradation of the mRNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death protein 4 (PDCD4) is a tumor suppressor responsible for the inhibition of cell growth, tumor invasion, metastasis, or induction of apoptosis [213]. It is localized in the nucleus of proliferating cells and binds to the eukaryotic initiation factor-4A (eIF4A) or eukaryotic translation initiation factor 4 G (eIF4G), inhibiting translation [214,215].…”
Section: Downregulation Of Programmed Cell Death Proteinmentioning
confidence: 99%
“…38 PDCD4 is an anti-carcinoma gene related to cell cycle and apoptosis. 39 Many researches had pointed out it could be used as a therapeutic target for various carcinomas. 40 Studies also pointed out that PDCD4 was low expressed in various carcinoma tissues such as gastric carcinoma and so on.…”
Section: Discussionmentioning
confidence: 99%